Cardiac Toxicity in Selective Serotonin Reuptake Inhibitor Users. (December 2015) - Lusetti, Monia; Licata, Manuela; Silingardi, Enrico; Reggiani Bonetti, Luca; Palmiere, Cristian
Abstract : Abstract: Several classes of recreational and prescription drugs have been associated with an increased risk of cardiovascular disease and the occurrence of arrhythmias, which may be involved in sudden deaths in chronic users even at therapeutic doses. The study presented herein focuses on pathological changes involving the heart, which may be caused by selective serotonin reuptake inhibitor use and their possible role in the occurrence of sudden cardiac death. A total of 40 cases were included in the study and were divided evenly into 2 groups: 20 cases of patients treated with selective serotonin reuptake inhibitors and 20 cases of sudden deaths involving patients void of any drug treatment. The first group included 16 patients treated with citalopram and 4 with sertraline. Autopsies, histology, biochemistry, and toxicology were performed in all cases. Pathological changes in selective serotonin reuptake inhibitor users consisted of various degrees of interstitial and perivascular fibrosis as well as a small degree of perineural fibrosis within the myocardium of the left ventricle. Within the limits of the small number of investigated cases, the results of this study seem to confirm former observations on this topic, suggesting that selective serotonin reuptake inhibitors may play a potential, causative role in the pathogenesis of sudden deaths in chronic users even at therapeutic concentrations.